97.9k views
2 votes
Which expression is equivalent to 6^–3?

A) –63

B) 36

C) 3sqrt/6

D) (1/6)^3

2 Answers

6 votes
Expression 6^–3 can be rewritten as:
1/6^3 = (1/6)^3

Therefore the answer is D

Hope that helps you
User Wudong
by
6.5k points
5 votes

Answer:


6^(-3)

Explanation:

Given :
6^(-3)

To Find: Which expression is equivalent to
6^(-3)

Solution:

Identity :
x ^(-1)=(1)/(x)

So,
6^(-3) =
((1)/(6))^3


6^(-3) =
((1)/(6))^3

So,
((1)/(6))^3 is equivalent to
6^(-3)

Thus Option D is correct.

User Toni Joe
by
6.5k points